Improvement of carbon black based polymer composite electrical conductivity with additions of MWCNT. (6th June 2016) - Burmistrov, I.; Gorshkov, N.; Ilinykh, I.; Muratov, D.; Kolesnikov, E.; Anshin, S.; Mazov, I.; Issi, J.-P.; Kusnezov, D.
Abstract: Owing to their exceptional mechanical, electrical and thermal properties, carbon nanotubes (CNTs) are ideal candidates for improving the performances of polymer composites. In the present work, we investigated the effect of CNT addition on the electrical conductivity of two types of carbon black (CB) filled polymer. Also, two different methods of compounding were applied and their effects are compared: mixing by a laboratory compounder Haake Rheomix Polylab and mixing by a twin-roller mixer. Composites containing a total of 10% by weight of different carbon fillers (CB, CNTs and their mixtures in a ratio of 8/2) were thus obtained, characterized by scanning electron microscopy and their frequency dependence of the electrical conductivity was measured. It is shown that the alternating current (AC) conductivities display two regions: a low frequency region of constant conductivity and a higher frequency region of increasing conductivity with increasing frequency (following the percolation scaling law). It was also observed that the samples compounded with twin-roller mixer exhibit a higher electrical conductivity than those obtained with the laboratory compounder. Moreover, the conductivity of the composites containing CNTs in addition to CB is found to be higher than the conductivity of the composites containing only CB.